ChemInform Abstract: A Strategy for Generating Alkyl Radicals from Aliphatic Esters and Lactones via Sequential Hydrolysis and Photoinduced Decarboxylation. Issue 29 (July 2015) - Saito, Hikaru; Kanetake, Takayuki; Osaka, Kazuyuki; Maeda, Kousuke; Morita, Toshio; Yoshimi, Yasuharu
Abstract Alkyl radicals generated from substrates (I) and (IX) react with acrylonitrile, tert‐dodecanethiol, or 1, 4‐dicyanobenzene to afford the corresponding addition, reduction, and substitution products.